Critical Newborn Screens in Double Heterozygotes of Inborn Errors of Metabolism-A Clinical Report and Recommendations - Katherine G. Langley; Elizabeth N. Chisholm; Brooke B. Spangler; Erin T. Strovel; Jennifer O. Macdonald; Samantha Schrier Vergano (MDPI AG, 2016)
The practice of newborn screening has been in place in the USA since the 1960s, with individual states initially screening for different numbers of disorders. In the early 2000s many efforts were made to standardize the various disorders being screened. Currently, there are at least 34 disorders that each state is mandated to include on their screening panel. Of those 34 disorders, the majority are inborn errors of metabolism (IEM) which include urea cycle disorders (UCD), citrullinemia (CIT) and argininosuccinic aciduria (ASA), as well as a number of fatty acid oxidation disorders. We present here four cases of infants who had critical newborn screens (NBS) in the Commonwealth of Virginia and underwent genetic testing because their clinical presentation and follow-up laboratory studies were not consistent with the disorder that was flagged by NBS. These newborns were found to be carriers for two different IEMs (in three cases) or compound heterozygotes (in one case). Currently no guidelines exist with respect to the appropriate way to manage these children who may or may not be symptomatic in the newborn period. We propose some general recommendations for management based on our experience with these four probands, and discuss the necessity for further conversation and collaboration between physicians encountering these not-so-infrequent presentations.